Platinum-silver synergistic rare earth oxide hydrogenation catalyst and preparation method thereof
Through the design of a rare earth oxide hydrogenation catalyst with platinum and silver synergistically, the problem of nanoparticles agglomeration of precious metal catalysts is solved by using support modification and interaction between metals, the structural stability and catalytic efficiency of the catalyst are improved, and the high selective hydrogenation reaction is achieved.
Patent Information
- Application Number
- CN202411765866.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
AI Technical Summary
The noble metal catalyst is prone to nanoparticle agglomeration in the hydrogenation reaction, resulting in a decrease in the dispersion of active components and a decrease in the catalytic performance.
The platinum-silver synergistic rare earth oxide hydrogenation catalyst is used to support rare earth oxides and composite metal oxides through a carbon-based support, and the structure and performance of the catalyst are optimized by supporting modification and metal interaction.
The structural stability and catalytic efficiency of the catalyst in the selective hydrogenation reaction of cinnamaldehyde are improved, and high selectivity for the target product is achieved.
Smart Images

Figure BDA0005168923320000081 
Figure BDA0005168923320000091
Abstract
Description
Technical Field
[0001] The invention relates to the field of precious metal catalysts, and in particular to a platinum-silver synergistic rare earth oxide hydrogenation catalyst and a preparation method thereof. Background Art
[0002] Catalysts can significantly change the rate of chemical reactions during chemical reactions, while their own quality and chemical properties do not change before and after the reaction. The presence of catalysts in the reaction can greatly improve the efficiency of chemical reactions, which can reduce industrial production costs and speed up production rates. Precious metals mainly refer to Ag, Au and Pt group metal elements. Precious metals usually have strong chemical stability and are not easy to react with other chemical substances. When precious metals reach a certain microscopic scale or distribution, they have a certain catalytic ability. Compared with non-precious metal catalysts, precious metal catalysts have better catalytic performance. Therefore, the preparation and application of precious metal catalysts are of great significance. At present, precious metals Pd, Pt, Ru, Ag, Rh and Au are often used to prepare precious metal catalysts. Among them, Pd and Pt metals are the most common in the field of catalysis. This is because the outermost d electron orbital of Pt and Pd atoms is unfilled, resulting in defect sites on the surface and easy to form covalent bonds with oxygen atoms or hydrogen atoms. This process is helpful to form a "transition state" or "active intermediate", so it has good catalytic activity for many oxidation reactions and hydrogenation reactions. In addition, precious metals have better sintering resistance, strong oxidation resistance and corrosion resistance. At the same time, precious metals have strong tolerance to common poisons in the reaction process, such as S, Cl and O, and are not easily poisoned, so they become important catalyst materials. The development of a low-cost, efficient heterogeneous catalyst to catalyze the selective hydrogenation of nitro compounds and biomass platform molecules is a research hotspot in the field of hydrogenation catalysis. Precious metal catalysts have shown excellent catalytic performance in many hydrogenation reactions, but they still face many problems and challenges, and there is a lot of room for optimization. In the preparation process of precious metal catalysts, agglomeration is easy to occur, which will reduce the dispersion of active components and lead to a decrease in the number of exposed active sites. Therefore, how to solve the dispersion of precious metal nanoparticles is a key issue in improving catalytic activity. Summary of the invention
[0003] Technical problem to be solved: The purpose of the present invention is to provide a platinum-silver synergistic rare earth oxide hydrogenation catalyst, which improves the catalytic performance of the catalyst in the cinnamaldehyde hydrogenation reaction by carrier modification and optimization of the interaction between the carrier and the metal.
[0004] Technical solution: A platinum-silver synergistic rare earth oxide hydrogenation catalyst, wherein the catalyst is composed of a carbon-based carrier loaded with rare earth oxide and a composite metal oxide, the composite metal oxide is obtained by calcining a layered composite metal hydroxide loaded with platinum and silver, and the rare earth oxide is lanthanum oxide. The preparation method of the above-mentioned platinum-silver synergistic rare earth oxide hydrogenation catalyst comprises the following steps: S1. Add cellulose to sodium hydroxide / urea / water, stir in an ice bath to dissolve, and obtain a cellulose solution; S2. The cellulose solution is quickly frozen by liquid nitrogen and then cold-dried to obtain a cellulose aerogel; S3. The cellulose aerogel is immersed in an aqueous solution of lanthanum nitrate, and then a sodium hydroxide solution is added dropwise to the solution, and an ultrasonic reaction is performed at room temperature to crystallize the aerogel to obtain a lanthanum-loaded aerogel; S4. Mix magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate, and add them to water to obtain a mixed salt solution; S5. After mixing calcium carbonate and sodium hydroxide, add them to water to obtain a mixed alkaline solution; S6. adding the lanthanum-loaded aerogel prepared in step S3 to the mixed salt solution prepared in step S4, and after soaking, dripping the mixed alkali solution prepared in step S5, ultrasonically reacting at room temperature, and then performing a crystallization reaction to obtain a PtAg-MgAl-LDH / La aerogel precursor; S7. Sintering the aerogel precursor prepared in step S6 to obtain a PtAg-MgAl-LDH / La2O3 hydrogenation catalyst. Preferably, the concentration of the cellulose solution in step S1 is 1.2-2 wt%. Preferably, the freeze-drying temperature in step S2 is -80 to -50°C, the time is 40-60h, and the pressure is 10-20 Pa. Preferably, the concentration of the lanthanum nitrate aqueous solution in step S3 is 0.1-0.5 mol / L, the ultrasonic reaction time is 30-60min, the crystallization temperature is 170-185°C, and the crystallization time is 20-30h. Preferably, in step S4, the molar ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate is 3:1:0.3-0.5:0.1-0.2. Preferably, the molar ratio of calcium carbonate to sodium hydroxide in step S5 is 4-5:1. Preferably, in step S6, the volume ratio of the mixed salt solution to the mixed alkali solution is 1:1, the ultrasonic reaction time is 30-60 min, the crystallization temperature is 55-68° C., and the time is 20-30 h. Preferably, the heating rate of sintering in step S7 is 5-10°C / min, and the temperature is raised to 520-580°C and then kept at this temperature for 4-6 hours. Beneficial effects: The platinum-silver synergistic rare earth oxide hydrogenation catalyst of the present invention has the following advantages: 1. In the present invention, the concentration of the cellulose solution is regulated to regulate the specific surface area, total pore volume and average pore size of the carbon-based support finally prepared, so that the noble metal has more binding sites on the support surface to improve the catalytic efficiency; 2. In the present invention, the ratio of platinum and silver is regulated to optimize the surface electronic structure of the catalyst, thereby improving the activation ability of specific reaction intermediates, and further controlling the selectivity of the final product. In the present invention, by introducing a specific ratio of platinum and silver, the electronic interaction between Pd and unsaturated carbon can be weakened, thereby controlling the depth of the hydrogenation chemical reaction and achieving high selectivity for the target product; 3. The mesh structure of the sintered MgAl-LDH in the present invention can confine the platinum and silver nano-alloy particles in a fixed position, inhibiting the agglomeration of the particles, thereby improving the structural stability of the catalyst of the present invention in the selective hydrogenation reaction of cinnamaldehyde and improving the catalytic efficiency. DETAILED DESCRIPTION The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments: Example 1 A method for preparing a platinum-silver synergistic rare earth oxide hydrogenation catalyst, the preparation method comprising the following steps: S1. Add cellulose to sodium hydroxide / urea / water, stir and dissolve in an ice bath to obtain a cellulose solution with a concentration of 1.2 wt%; S2. The cellulose solution was quickly frozen in liquid nitrogen and then cold-dried at a freeze-drying temperature of -80°C for 40 hours at a pressure of 10 Pa to obtain a cellulose aerogel; S3. The cellulose aerogel was immersed in a 0.1 mol / L lanthanum nitrate aqueous solution, and then a sodium hydroxide solution was added dropwise to the solution. The aerogel was subjected to ultrasonic reaction at room temperature for 30 min, and the aerogel was crystallized at 170 ° C for 30 h to obtain a lanthanum-loaded aerogel; S4. After mixing magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate, the molar ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate is 3:1:0.3:0.1, and adding it to water to obtain a mixed salt solution; S5. After mixing calcium carbonate and sodium hydroxide, the molar ratio of calcium carbonate and sodium hydroxide is 4:1, and added to water to obtain a mixed alkaline solution; S6. Add the lanthanum-loaded aerogel prepared in step S3 to the mixed salt solution prepared in step S4, and after soaking, dropwise add the mixed alkali solution prepared in step S5, wherein the volume ratio of the mixed salt solution to the mixed alkali solution is 1:1, and ultrasonically react at room temperature for 30 minutes, and then crystallize at 55° C. for 20 hours to obtain a PtAg-MgAl-LDH / La aerogel precursor; S7. Sinter the aerogel precursor prepared in step S6 at a heating rate of 5°C / min, heat to 520°C and keep the temperature for 6 hours to obtain a PtAg-MgAl-LDH / La2O3 hydrogenation catalyst. Example 2 A method for preparing a platinum-silver synergistic rare earth oxide hydrogenation catalyst, the preparation method comprising the following steps: S1. Add cellulose to sodium hydroxide / urea / water, stir and dissolve in an ice bath to obtain a cellulose solution with a concentration of 2 wt%; S2. The cellulose solution was quickly frozen in liquid nitrogen and then cold-dried at a freeze-drying temperature of -50°C for 60 hours at a pressure of 20 Pa to obtain a cellulose aerogel; S3. The cellulose aerogel was immersed in a 0.5 mol / L lanthanum nitrate aqueous solution, and then a sodium hydroxide solution was added dropwise to the solution. The aerogel was subjected to ultrasonic reaction at room temperature for 60 min, and the aerogel was crystallized at 185 ° C for 20 h to obtain a lanthanum-loaded aerogel; S4. After mixing magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate, the molar ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate is 3:1:0.5:0.2, and adding it to water to obtain a mixed salt solution; S5. After mixing calcium carbonate and sodium hydroxide, the molar ratio of calcium carbonate and sodium hydroxide is 5:1, and added to water to obtain a mixed alkaline solution; S6. Add the lanthanum-loaded aerogel prepared in step S3 to the mixed salt solution prepared in step S4, and after soaking, dropwise add the mixed alkali solution prepared in step S5, wherein the volume ratio of the mixed salt solution to the mixed alkali solution is 1:1, and ultrasonically react at room temperature for 60 minutes, and then crystallize at 68° C. for 30 hours to obtain a PtAg-MgAl-LDH / La aerogel precursor; S7. Sinter the aerogel precursor prepared in step S6 at a heating rate of 10°C / min, heat to 580°C and keep the temperature for 6 hours to obtain a PtAg-MgAl-LDH / La2O3 hydrogenation catalyst. Example 3 A method for preparing a platinum-silver synergistic rare earth oxide hydrogenation catalyst, the preparation method comprising the following steps: S1. Add cellulose to sodium hydroxide / urea / water, stir in an ice bath to dissolve, and obtain a cellulose solution with a concentration of 1.4 wt%; S2. The cellulose solution was quickly frozen in liquid nitrogen and then cold-dried at a freeze-drying temperature of -70°C for 55 hours at a pressure of 15 Pa to obtain a cellulose aerogel; S3. The cellulose aerogel was immersed in a 0.2 mol / L lanthanum nitrate aqueous solution, and then a sodium hydroxide solution was added dropwise to the solution. The aerogel was subjected to ultrasonic reaction at room temperature for 40 min, and the aerogel was crystallized at 175 ° C for 27 h to obtain a lanthanum-loaded aerogel; S4. After mixing magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate, the molar ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate is 3:1:0.35:0.12, and adding it to water to obtain a mixed salt solution; S5. After mixing calcium carbonate and sodium hydroxide, the molar ratio of calcium carbonate and sodium hydroxide was 4.2: 1, and added to water to obtain a mixed alkaline solution; S6. Add the lanthanum-loaded aerogel prepared in step S3 to the mixed salt solution prepared in step S4, and after soaking, dropwise add the mixed alkali solution prepared in step S5, wherein the volume ratio of the mixed salt solution to the mixed alkali solution is 1:1, and ultrasonically react at room temperature for 50 minutes, and then crystallize at 50° C. for 27 hours to obtain a PtAg-MgAl-LDH / La aerogel precursor; S7. Sinter the aerogel precursor prepared in step S6 at a heating rate of 6°C / min, heat to 530°C and keep the temperature for 4.5h to obtain a PtAg-MgAl-LDH / La2O3 hydrogenation catalyst. Example 4 A method for preparing a platinum-silver synergistic rare earth oxide hydrogenation catalyst, the preparation method comprising the following steps: S1. Add cellulose to sodium hydroxide / urea / water, stir in an ice bath to dissolve, and obtain a cellulose solution with a concentration of 1.8 wt%; S2. The cellulose solution was quickly frozen in liquid nitrogen and then cold-dried at a freeze-drying temperature of -60°C, a time of 45h, and a pressure of 15Pa to obtain a cellulose aerogel; S3. The cellulose aerogel was immersed in a 0.4 mol / L lanthanum nitrate aqueous solution, and then a sodium hydroxide solution was added dropwise to the solution. The aerogel was subjected to ultrasonic reaction at room temperature for 50 min, and the aerogel was crystallized at 180 ° C for 24 h to obtain a lanthanum-loaded aerogel; S4. After mixing magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate, the molar ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate is 3:1:0.45:0.16, and adding it to water to obtain a mixed salt solution; S5. After mixing calcium carbonate and sodium hydroxide, the molar ratio of calcium carbonate and sodium hydroxide was 4.7: 1, and added to water to obtain a mixed alkaline solution; S6. Add the lanthanum-loaded aerogel prepared in step S3 to the mixed salt solution prepared in step S4, and after soaking, dropwise add the mixed alkali solution prepared in step S5, wherein the volume ratio of the mixed salt solution to the mixed alkali solution is 1:1, and ultrasonically react at room temperature for 40 minutes, and then crystallize at 65° C. for 24 hours to obtain a PtAg-MgAl-LDH / La aerogel precursor; S7. Sinter the aerogel precursor prepared in step S6 at a heating rate of 9°C / min, heat to 560°C and keep the temperature for 5.5h to obtain a PtAg-MgAl-LDH / La2O3 hydrogenation catalyst. Example 5 A method for preparing a platinum-silver synergistic rare earth oxide hydrogenation catalyst, the preparation method comprising the following steps: S1. Add cellulose to sodium hydroxide / urea / water, stir in an ice bath to dissolve, and obtain a cellulose solution with a concentration of 1.5 wt%; S2. The cellulose solution was quickly frozen in liquid nitrogen and then cold-dried at a freeze-drying temperature of -65°C for 50 hours at a pressure of 15 Pa to obtain a cellulose aerogel; S3. The cellulose aerogel was immersed in a 0.3 mol / L lanthanum nitrate aqueous solution, and then a sodium hydroxide solution was added dropwise to the solution. The aerogel was subjected to ultrasonic reaction at room temperature for 45 min, and the aerogel was crystallized at 175 ° C for 25 h to obtain a lanthanum-loaded aerogel; S4. After mixing magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate, the molar ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate is 3:1:0.4:0.15, and adding it to water to obtain a mixed salt solution; S5. After mixing calcium carbonate and sodium hydroxide, the molar ratio of calcium carbonate and sodium hydroxide was 4.5: 1, and added to water to obtain a mixed alkaline solution; S6. Add the lanthanum-loaded aerogel prepared in step S3 to the mixed salt solution prepared in step S4, and after soaking, dropwise add the mixed alkali solution prepared in step S5, wherein the volume ratio of the mixed salt solution to the mixed alkali solution is 1:1, and ultrasonically react at room temperature for 45 minutes, and then crystallize at 60° C. for 25 hours to obtain a PtAg-MgAl-LDH / La aerogel precursor; S7. Sinter the aerogel precursor prepared in step S6 at a heating rate of 8°C / min, heat to 550°C and keep the temperature for 5h to obtain a PtAg-MgAl-LDH / La2O3 hydrogenation catalyst. Comparative Example 1 A method for preparing a platinum-silver synergistic rare earth oxide hydrogenation catalyst, the preparation method comprising the following steps: S1. Add cellulose to sodium hydroxide / urea / water, stir and dissolve in an ice bath to obtain a cellulose solution having a concentration of 4 wt%; S2. The cellulose solution was quickly frozen in liquid nitrogen and then cold-dried at a freeze-drying temperature of -65°C for 50 hours at a pressure of 15 Pa to obtain a cellulose aerogel; S3. The cellulose aerogel was immersed in a 0.3 mol / L lanthanum nitrate aqueous solution, and then a sodium hydroxide solution was added dropwise to the solution. The aerogel was subjected to ultrasonic reaction at room temperature for 45 min, and the aerogel was crystallized at 175 ° C for 25 h to obtain a lanthanum-loaded aerogel; S4. After mixing magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate, the molar ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate is 3:1:0.4:0.15, and adding it to water to obtain a mixed salt solution; S5. After mixing calcium carbonate and sodium hydroxide, the molar ratio of calcium carbonate and sodium hydroxide was 4.5: 1, and added to water to obtain a mixed alkaline solution; S6. Add the lanthanum-loaded aerogel prepared in step S3 to the mixed salt solution prepared in step S4, and after soaking, dropwise add the mixed alkali solution prepared in step S5, wherein the volume ratio of the mixed salt solution to the mixed alkali solution is 1:1, and ultrasonically react at room temperature for 45 minutes, and then crystallize at 60° C. for 25 hours to obtain a PtAg-MgAl-LDH / La aerogel precursor; S7. Sinter the aerogel precursor prepared in step S6 at a heating rate of 8°C / min, heat to 550°C and keep the temperature for 5h to obtain a PtAg-MgAl-LDH / La2O3 hydrogenation catalyst. Table 1 Structural characteristic constants of Example 5 and Comparative Example 1 <![CDATA[Specific surface area m 2 / g]]> <![CDATA[Total pore volume cm 3 / g]]> Average pore size nm Example 5 149.8 0.42 11.2 Comparative Example 1 113.5 0.28 3.2 Comparative Example 2 A method for preparing a platinum-silver synergistic rare earth oxide hydrogenation catalyst, the preparation method comprising the following steps: S1. Add cellulose to sodium hydroxide / urea / water, stir in an ice bath to dissolve, and obtain a cellulose solution with a concentration of 1.5 wt%; S2. The cellulose solution was quickly frozen in liquid nitrogen and then cold-dried at a freeze-drying temperature of -65°C for 50 hours at a pressure of 15 Pa to obtain a cellulose aerogel; S3. After mixing magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate, the molar ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate is 3:1:0.4:0.15, and adding it to water to obtain a mixed salt solution; S4. After mixing calcium carbonate and sodium hydroxide, the molar ratio of calcium carbonate and sodium hydroxide was 4.5: 1, and added to water to obtain a mixed alkaline solution; S5. Add the aerogel prepared in step S2 to the mixed salt solution prepared in step S3, soak, and then dropwise add the mixed alkali solution prepared in step S4, wherein the volume ratio of the mixed salt solution to the mixed alkali solution is 1:1, and ultrasonically react at room temperature for 45 minutes, and then crystallize at 60° C. for 25 hours to obtain a PtAg-MgAl-LDH aerogel precursor; S6. Sinter the aerogel precursor prepared in step S5 at a heating rate of 8°C / min, heat to 550°C and keep the temperature for 5h to obtain a PtAg-MgAl-LDH / La2O3 hydrogenation catalyst. Comparative Example 3 A method for preparing a platinum-silver synergistic rare earth oxide hydrogenation catalyst, the preparation method comprising the following steps: S1. Add cellulose to sodium hydroxide / urea / water, stir in an ice bath to dissolve, and obtain a cellulose solution with a concentration of 1.5 wt%; S2. The cellulose solution was quickly frozen in liquid nitrogen and then cold-dried at a freeze-drying temperature of -65°C for 50 hours at a pressure of 15 Pa to obtain a cellulose aerogel; S3. The cellulose aerogel was immersed in a 0.3 mol / L lanthanum nitrate aqueous solution, and then a sodium hydroxide solution was added dropwise to the solution. The aerogel was subjected to ultrasonic reaction at room temperature for 45 min, and the aerogel was crystallized at 175 ° C for 25 h to obtain a lanthanum-loaded aerogel; S4. After mixing magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and platinum nitrate, the molar ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and platinum nitrate is 3:1:0.4, and adding it to water to obtain a mixed salt solution; S5. After mixing calcium carbonate and sodium hydroxide, the molar ratio of calcium carbonate and sodium hydroxide was 4.5: 1, and added to water to obtain a mixed alkaline solution; S6. Add the lanthanum-loaded aerogel prepared in step S3 to the mixed salt solution prepared in step S4, and after soaking, dropwise add the mixed alkali solution prepared in step S5, wherein the volume ratio of the mixed salt solution to the mixed alkali solution is 1:1, and ultrasonically react at room temperature for 45 minutes, and then crystallize at 60° C. for 25 hours to obtain a Pt-MgAl-LDH / La aerogel precursor; S7. Sinter the aerogel precursor prepared in step S6 at a heating rate of 8°C / min, heat to 550°C and keep the temperature for 5h to obtain a Pt-MgAl-LDH / La2O3 hydrogenation catalyst. Comparative Example 4 A method for preparing a platinum-silver synergistic rare earth oxide hydrogenation catalyst, the preparation method comprising the following steps: S1. Add cellulose to sodium hydroxide / urea / water, stir in an ice bath to dissolve, and obtain a cellulose solution with a concentration of 1.5 wt%; S2. The cellulose solution was quickly frozen in liquid nitrogen and then cold-dried at a freeze-drying temperature of -65°C for 50 hours at a pressure of 15 Pa to obtain a cellulose aerogel; S3. The cellulose aerogel was immersed in a 0.3 mol / L lanthanum nitrate aqueous solution, and then a sodium hydroxide solution was added dropwise to the solution. The aerogel was subjected to ultrasonic reaction at room temperature for 45 min, and the aerogel was crystallized at 175 ° C for 25 h to obtain a lanthanum-loaded aerogel; S4. After mixing magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate, the molar ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate is 3:1:1:0.15, and adding it to water to obtain a mixed salt solution; S5. After mixing calcium carbonate and sodium hydroxide, the molar ratio of calcium carbonate and sodium hydroxide was 4.5: 1, and added to water to obtain a mixed alkaline solution; S6. Add the lanthanum-loaded aerogel prepared in step S3 to the mixed salt solution prepared in step S4, and after soaking, dropwise add the mixed alkali solution prepared in step S5, wherein the volume ratio of the mixed salt solution to the mixed alkali solution is 1:1, and ultrasonically react at room temperature for 45 minutes, and then crystallize at 60° C. for 25 hours to obtain a PtAg-MgAl-LDH / La aerogel precursor; S7. Sinter the aerogel precursor prepared in step S6 at a heating rate of 8°C / min, heat to 550°C and keep the temperature for 5h to obtain a PtAg-MgAl-LDH / La2O3 hydrogenation catalyst. Comparative Example 5 A method for preparing a platinum-silver synergistic rare earth oxide hydrogenation catalyst, the preparation method comprising the following steps: S1. Add cellulose to sodium hydroxide / urea / water, stir in an ice bath to dissolve, and obtain a cellulose solution with a concentration of 1.5 wt%; S2. The cellulose solution was quickly frozen in liquid nitrogen and then cold-dried at a freeze-drying temperature of -65°C for 50 hours at a pressure of 15 Pa to obtain a cellulose aerogel; S3. The cellulose aerogel was immersed in a 0.3 mol / L lanthanum nitrate aqueous solution, and then a sodium hydroxide solution was added dropwise to the solution. The aerogel was subjected to ultrasonic reaction at room temperature for 45 min, and the aerogel was crystallized at 175 ° C for 25 h to obtain a lanthanum-loaded aerogel; S4. After mixing magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate, the molar ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate is 3:1:0.4:0.4, and adding it to water to obtain a mixed salt solution; S5. After mixing calcium carbonate and sodium hydroxide, the molar ratio of calcium carbonate and sodium hydroxide was 4.5: 1, and added to water to obtain a mixed alkaline solution; S6. Add the lanthanum-loaded aerogel prepared in step S3 to the mixed salt solution prepared in step S4, and after soaking, dropwise add the mixed alkali solution prepared in step S5, wherein the volume ratio of the mixed salt solution to the mixed alkali solution is 1:1, and ultrasonically react at room temperature for 45 minutes, and then crystallize at 60° C. for 25 hours to obtain a PtAg-MgAl-LDH / La aerogel precursor; S7. Sinter the aerogel precursor prepared in step S6 at a heating rate of 8°C / min, heat to 550°C and keep the temperature for 5h to obtain a PtAg-MgAl-LDH / La2O3 hydrogenation catalyst. Comparative Example 6 A method for preparing a platinum-silver synergistic rare earth oxide hydrogenation catalyst, the preparation method comprising the following steps: S1. Add cellulose to sodium hydroxide / urea / water, stir in an ice bath to dissolve, and obtain a cellulose solution with a concentration of 1.5 wt%; S2. The cellulose solution was quickly frozen in liquid nitrogen and then cold-dried at a freeze-drying temperature of -65°C for 50 hours at a pressure of 15 Pa to obtain a cellulose aerogel; S3. The cellulose aerogel was immersed in a 0.3 mol / L cerium nitrate aqueous solution, and then a sodium hydroxide solution was added dropwise to the solution. The aerogel was subjected to ultrasonic reaction at room temperature for 45 min, and the aerogel was crystallized at 175 ° C for 25 h to obtain a cerium-loaded aerogel; S4. After mixing magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate, the molar ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate is 3:1:0.4:0.15, and adding it to water to obtain a mixed salt solution; S5. After mixing calcium carbonate and sodium hydroxide, the molar ratio of calcium carbonate and sodium hydroxide was 4.5: 1, and added to water to obtain a mixed alkaline solution; S6. Add the cerium-loaded aerogel prepared in step S3 to the mixed salt solution prepared in step S4, and after soaking, dropwise add the mixed alkali solution prepared in step S5, wherein the volume ratio of the mixed salt solution to the mixed alkali solution is 1:1, and ultrasonically react at room temperature for 45 minutes, and then crystallize at 60° C. for 25 hours to obtain a PtAg-MgAl-LDH / Ce aerogel precursor; S7. Sinter the aerogel precursor prepared in step S6 at a heating rate of 8°C / min, heat to 550°C and keep the temperature for 5h to obtain a PtAg-MgAl-LDH / CeO2 hydrogenation catalyst. The catalysts prepared in the examples and comparative examples were used to catalyze the selective hydrogenation of cinnamaldehyde to prepare cinnamyl alcohol. The specific catalytic effects are shown in Table 2 below: Table 2 Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A platinum-silver synergistic rare earth oxide hydrogenation catalyst, characterized in that: The catalyst is composed of a carbon-based carrier loaded with rare earth oxide and composite metal oxide, the composite metal oxide is obtained by calcining a layered composite metal hydroxide loaded with platinum and silver, and the rare earth oxide is lanthanum oxide.
2. The method for preparing the platinum-silver synergistic rare earth oxide hydrogenation catalyst according to claim 1, characterized in that: The preparation method comprises the following steps: S1. Add cellulose to sodium hydroxide / urea / water, stir in an ice bath to dissolve, and obtain a cellulose solution; S2. The cellulose solution is quickly frozen by liquid nitrogen and then cold-dried to obtain a cellulose aerogel; S3. The cellulose aerogel is immersed in an aqueous solution of lanthanum nitrate, and then a sodium hydroxide solution is added dropwise to the solution, and an ultrasonic reaction is performed at room temperature to crystallize the aerogel to obtain a lanthanum-loaded aerogel; S4. Mix magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate, and add them to water to obtain a mixed salt solution; S5. After mixing calcium carbonate and sodium hydroxide, add them to water to obtain a mixed alkaline solution; S6. adding the lanthanum-loaded aerogel prepared in step S3 to the mixed salt solution prepared in step S4, and after soaking, dripping the mixed alkali solution prepared in step S5, ultrasonically reacting at room temperature, and then performing a crystallization reaction to obtain a PtAg-MgAl-LDH / La aerogel precursor; S7. Sintering the aerogel precursor prepared in step S6 to obtain a PtAg-MgAl-LDH / La2O3 hydrogenation catalyst.
3. The method for preparing the platinum-silver synergistic rare earth oxide hydrogenation catalyst according to claim 2, characterized in that: The concentration of the cellulose solution in step S1 is 1.2-2 wt %.
4. The method for preparing the platinum-silver synergistic rare earth oxide hydrogenation catalyst according to claim 2, characterized in that: The freeze drying temperature in step S2 is -80 to -50°C, the time is 40 to 60 hours, and the pressure is 10 to 20 Pa.
5. The method for preparing the platinum-silver synergistic rare earth oxide hydrogenation catalyst according to claim 2, characterized in that: In step S3, the concentration of the lanthanum nitrate aqueous solution is 0.1-0.5 mol / L, the ultrasonic reaction time is 30-60 min, the crystallization temperature is 170-185° C., and the crystallization time is 20-30 h.
6. The method for preparing the platinum-silver synergistic rare earth oxide hydrogenation catalyst according to claim 2, characterized in that: In step S4, the molar ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, platinum nitrate and silver nitrate is 3:1:0.3-0.5:0.1-0.
2.
7. The method for preparing the platinum-silver synergistic rare earth oxide hydrogenation catalyst according to claim 2, characterized in that: The molar ratio of calcium carbonate to sodium hydroxide in step S5 is 4-5:
1.
8. The method for preparing the platinum-silver synergistic rare earth oxide hydrogenation catalyst according to claim 2, characterized in that: In step S6, the volume ratio of the mixed salt solution to the mixed alkali solution is 1:1, the ultrasonic reaction time is 30-60 minutes, the crystallization temperature is 55-68° C., and the time is 20-30 hours.
9. The method for preparing the platinum-silver synergistic rare earth oxide hydrogenation catalyst according to claim 2, characterized in that: The sintering temperature in step S7 is increased at a rate of 5-10°C / min, and the temperature is increased to 520-580°C and then maintained for 4-6 hours.